PPAT Responsibilities in Credit Agreements with Mortgage Guarantee - Noor, Aslan; Kurniawan, Kunkun; Ruhima, Asep Rudi t; Utama, Fajar Prawira; Affandy, Muhammad Kurnia (International Journal of Science and Society, 2024)
A credit agreement with mortgage rights is a legal arrangement that involves the lender, borrower, and a PPAT, who is tasked with formalizing the land deed as a legal document outlining the rights and obligations of all parties involved. The objective of this study is to examine the obligations of Land Deed Drafting Officials (PPAT) concerning the execution of credit agreements with collateral rights. Employing a normative legal approach, the findings emphasize the pivotal role of PPAT in administering mortgage rights within such agreements. PPAT not only acts as the executor of the Deed of Granting Mortgage Rights (APHT) but also shoulders responsibilities including verifying legal data, ensuring document completeness, and adhering to legal regulations. Moreover, the study underscores the significance of timeliness in the registration procedure, setting a deadline of 7 working days post-signing of the APHT. Any delays in registration, particularly stemming from PPAT negligence, may entail legal ramifications and pose risks for creditors. In summary, the research outcomes offer a thorough understanding of the vital role played by PPAT in overseeing the encumbrance of Mortgage Rights, thereby enhancing security and legal assurance in credit transactions with Mortgage Guarantee.